Outcome assessment in veterinary pain studies: a pain in animals workshop (PAW) perspective - Brown, D. C.; Coetzee, J.; Gill, M.; Johnson, C.; Mohapatra, D. P.; Oshinsky, M. L.; Robertson, S. A.; Smith, E. R.; Lascelles, B. D. X. (Frontiers in Pain Research, 2025)
Biennially, the Pain in Animals Workshop (PAW) forum brings together scientists and clinicians to focus, across veterinary species and humans, on our shared passion of improving health through our ability to recognize and monitor pain. This collaboration has been instrumental in sharing current knowledge, identifying gaps, and aligning on the best paths forward in this challenging space. At the 2023 PAW held at the National Institutes of Health, Dr Dottie Brown delivered the inaugural Dr. Michele Sharkey PAW Lecture: “Outcome Assessment in Veterinary Pain Studies: The Yellow Brick Road Continues”. This perspectives article captures the content of that inaugural lecture and provides a reflection on how the PAW forums have been integral to the most recent wave of knowledge gain and awareness.